Stromal Myofibroblasts in Correlation With Inflammation and Impacted Tooth in Odontogenic Cysts: An Immunohistochemical Comparative Study - Martins, Karina Helen; Barbeiro, Camila de Oliveira [UNESP]; Barbeiro, Roberto Henrique [UNESP]; Anbinder, Ana Lia [UNESP]; Guardia, Rafaella Souza [UNESP]; Silva, Evânio Vilela [UNESP]; Reyes, Magdalena Raquel Torres; Javaroni, Júlia Biliato; Esquiche, Jorge; de Rossi, Andiara (Research Square Platform, 2023)
Aim
Stromal myofibroblasts may act favoring growth and progression of odontogenic lesions, notably odontogenic keratocyst (OKC). While little explored the associated inflammation, it has been shown that OKC associated with an impacted tooth has a tendency toward rapid growth. Whether this finding is associated with the differential expression of myofibroblast immunomarkers, is unknown.
Materials and methods
Thirteen cases of each, pericoronal follicle (PF), inflamed dentigerous cyst (iDC), noninflamed DC (nDC), OKC associated with (OKC-A) or not associated (OKC-N) with impacted tooth, were evaluated through vimentin, α-SMA, calponin and h-caldesmon immunomarkers The data obtained were analyzed using the Shapiro-Wilk, Kruskal-Wallis and Dwass-Steel-Critchlow-Fligner Multiple Comparisons tests, with p < 0.05 being considered statistically significant.
Results
All cases were vimentin positive, with few cases exhibiting mild expression. All PFs were α-SMA negative. OKCs showed significant higher expression of α-SMA than DCs (p < 0.05). With similar expression between DC groups, the α-SMA expression was higher in OKC-A than OKC-N (p = 0.882). Also, the mean age of OKC-A was significantly lower than OKC-N patients. Only 4 cases (1 iDC, 3 OKC-N) showed mild expression of calponin. All cases were h-caldesmon negative.
Conclusions
Our results suggest lack of myofibroblastic differentiation in PFs. Inflammation does not seem to influence the myofibroblast population in DCs. Although not significant, a higher expression of α-SMA can explain the clinicopathological features of OKC-A patients. Calponin seems not to be a reliable marker for myofibroblasts in these cases.
Clinical relevance
Lack of myofibroblastic differentiation seems to be consistent with the nature and function of PF. OKC (still, OKC-A than OKC-N) presents higher α-SMA expression than DC, which can help to explain its distinctive growth potentials.